PENINGKATAN KEMAMPUAN MENULIS KARYA ILMIAH DENGAN MODEL DISCOVERY BASED LEARNING PADA SISWA KELAS XI - Yunita, Maulidia; Martono, Martono; Lasmono, Djon (Universitas Tanjungpura, 2024)
This research is motivated by the low ability of high school students to write scientific papers, attributed to the use of inappropriate teaching methods. The lack of achievement of the Minimum Completeness Criteria (KKM) by approximately 60% serves as the rationale for conducting this study. The research aims to describe the Learning Implementation Plan (RPP) in designing scientific work texts, explore the implementation of learning using the Discovery Based Learning method, and assess the results and evaluation of learning in designing scientific work texts. The study was conducted among students of class XI MIPA 1 at SMA Muhammadiyah 1 Pontianak. The research method employed the Classroom Action Research (CAR) approach, consisting of two cycles involving planning, action, observation, and reflection. Data collection involved both test and non-test instruments, such as observation sheets, documentation, and assessment of learning outcomes. The research findings indicate a significant improvement in writing scientific work texts through the utilization of the Discovery Based Learning method. All students, totaling 100%, achieved or exceeded the school's set KKM (score of 76). Consequently, this study concludes that selecting an appropriate teaching method, such as Discovery Based Learning, has the potential to enhance learning outcomes, enabling the attainment of desired learning objectives. This step provides an indication that the use of the right methods can impact an increase in students' learning outcomes in scientific paper writing.